The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1998
DOI: 10.18388/abp.1998_4202
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of the yeast HAM1 gene prevents 6-N-hydroxylaminopurine mutagenesis in Escherichia coli.

Abstract: The base analogue 6-N-hydroxylaminopurine (HAP) is a potent mutagen in a variety of prokaryotic and eukaryotic organisms. Mutations in the yeast ham1 gene render the cells hypersensitive to the mutagenic effect of HAP. We have found that this gene has homologues in a variety of organisms from bacteria to man. We have overexpressed yeast Ham1p in E. coli. We demonstrate that under conditions when this protein constitutes approximately 30% of cellular protein, the host strain is protected both from toxic and mut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…Carlsson et al () have previously shown that overexpression of the Ham1 gene in yeast protects against the exogenous supply of the non‐canonical, mutagenic pyrimidine nucleoside 5‐fluorouracil (5‐FU). The yeast Ham1 gene can protect against several non‐canonical nucleosides, including 6‐ N ‐hydroxylaminopurine (Kozmin et al , ; Noskov et al , ), 5‐fluorocytosine, and 6‐azauracil (Carlsson et al , ). To investigate whether U/CBSV Ham1 proteins can also provide protection from 5‐FU, resistance assays were performed.…”
Section: Resultsmentioning
confidence: 99%
“…Carlsson et al () have previously shown that overexpression of the Ham1 gene in yeast protects against the exogenous supply of the non‐canonical, mutagenic pyrimidine nucleoside 5‐fluorouracil (5‐FU). The yeast Ham1 gene can protect against several non‐canonical nucleosides, including 6‐ N ‐hydroxylaminopurine (Kozmin et al , ; Noskov et al , ), 5‐fluorocytosine, and 6‐azauracil (Carlsson et al , ). To investigate whether U/CBSV Ham1 proteins can also provide protection from 5‐FU, resistance assays were performed.…”
Section: Resultsmentioning
confidence: 99%
“…One CDS in pBKRR.14 matched with a periplasmic component of the Tol biopolymer transport system (Eick‐Helmerich and Braun, 1989). pBKRR.09 contained two coding sequences resembling a Ham1 family protein and a xenobiotic responsive element (XRE‐like protein) from the anaerobic archaea Sulfolobus solfataricus and Pyrococcus horikosh , which are involved in the protection of prokaryotic and eukaryotic organisms from toxic and mutagenic chemicals (Kozmin et al ., 1998), and in the expression of cytochrome P450 in response to xenobiotic inducers and dioxin respectively (Jones et al ., 1985; Fujisawa‐Sehara et al ., 1986).…”
Section: Resultsmentioning
confidence: 99%
“…In E. coli , HAP hypersensitivity was observed in strains carrying a deletion of the uvrB‐bio chromosomal region (Pavlov et al ., 1996). The Δ( uvrB‐bio ) strains were also AHAP‐hypermutable and sensitive to growth inhibition or killing by hydroxylamine (Pavlov et al ., 1996; Kozmin et al ., 1998b). Likewise, Salmonella strains carrying a corresponding deletion of the uvrB‐bio region proved hypermutable by AHAP and N 4 ‐hydroxycytidine (Janion, 1978; Janion, 1979; Janion and Myszkowska, 1981).…”
Section: Introductionmentioning
confidence: 99%